Customer Perception Towards Online Shopping - Agarwal, Varsha (International Journal of Novel Research and Development, 2022)
The traditional means by which consumers shop for and purchase goods and services has been altered by the internet extensively during and after the pandemic. Going digital is the latest trend in this age and time that is changing at a fast rate. To keep ahead of the competition, every- small or big - business is increasingly attempting to establish an online presence. Online comparison shopping for prices, product features, and post-purchase support services is another way that consumers use the internet. Online shopping, sometimes known as e-shopping, is a type of electronic commerce that enables customers to make direct purchases from merchants over the Internet using a computer browser. Online shopping is more popular with consumers since it saves time and offers a wider variety of products than traditional offline stores. And maybe most importantly, receiving items at home eliminates the need for travel.
ISME
Keywords: Online shopping; e-shopping; consumer; online presence; internet